"Do You Really Want to be Disappointed?": Adoptees' Expectations and Violations During Birth Family Contact. Issue 2 (15th March 2023) - Anzur, Christine K.
ABSTRACT: The current study used an Expectancy Violations Theory (EVT) framework to explore the expectations that adult adoptees have as they begin to make contact with birth family members. Thirty-two semi-structured interviews with adoptees revealed expectations for birth family contact, violations that occurred during contact, and effects of those violations. Largely, expectations were negative, as adoptees were concerned that contact would (a) cause problems for the birth family member, (b) result in a second rejection, or (c) reveal negative information about the birth family member. Adoptees experienced both positive and negative violations when they made contact, resulting in feelings of uncertainty. These results shed light on the complicated process of making birth family contact.